Disrupted nocturnal melatonin in autism: Association with tumor necrosis factor and sleep disturbances - da Silveira Cruz-Machado, Sanseray; Guissoni Campos, Leila Maria; Fadini, Cintia Cristina [UNESP]; Anderson, George; Markus, Regina P.; Pinato, Luciana [UNESP] (Wiley, 2021)
Sleep disturbances, abnormal melatonin secretion, and increased inflammation are aspects of autism spectrum disorder (ASD) pathophysiology. The present study evaluated the daily urinary 6-sulfatoxymelatonin (aMT6s) excretion profile and the salivary levels of tumor necrosis factor (TNF) and interleukin-6 (IL-6) in 20 controls and 20 ASD participants, as well as correlating these measures with sleep disturbances. Although 60% of ASD participants showed a significant night-time rise in aMT6s excretion, this rise was significantly attenuated, compared to controls (P <.05). The remaining 40% of ASD individuals showed no significant increase in nocturnal aMT6s. ASD individuals showed higher nocturnal levels of saliva TNF, but not IL-6. Dysfunction in the initiation and maintenance of sleep, as indicated by the Sleep Disturbance Scale for Children, correlated with night-time aMT6s excretion (r = −.28, P <.05). Dysfunction in sleep breathing was inversely correlated with aMT6s (r = −.31, P <.05) and positively associated with TNF level (r =.42, P <.01). Overall such data indicate immune-pineal axis activation, with elevated TNF but not IL-6 levels associated with disrupted pineal melatonin release and sleep dysfunction in ASD. It is proposed that circadian dysregulation in ASD is intimately linked to heightened immune-inflammatory activity. Such two-way interactions of the immune-pineal axis may underpin many aspects of ASD pathophysiology, including sleep disturbances, as well as cognitive and behavioral alterations.
Keywords: 6-sulfatoxymelatonin; autism spectrum disorder; behavior; cytokines; immune-pineal axis; melatonin; neuroinflammation